When decentralising, put the fisherfolk and farmers first - Laly, Marcellin (Technical Centre for Agricultural and Rural Cooperation, 2002)
Throughout Africa, the dual influences of globalisation and decentralisation are increasingly gaining a foothold. As a result, agricultural production has become a high-risk activity, a situation made worse by two key handicaps: natural disasters...